1983
DOI: 10.1164/arrd.1983.127.5.650
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Melioidosis Caused by a Multiresistant Strain in an Immunocompromised Host with Third Generation Cephalosporins1

Abstract: A 32-yr-old woman with active systemic lupus erythematosus receiving prednisone and azathioprine developed lung abscesses of the right lower lobe caused by Pseudomonas pseudomallei, which was resistant concomitantly to chloramphenicol, co-trimoxazole, and tetracycline, but highly sensitive to a new cephalosporin, ceftazidime. Melioidosis was treated successfully with lobectomy and parenteral ceftazidime, which was given for 2 months without major side effects. Ceftazidime, being bactericidal, may be more promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…These drugs are also associated with serious renal and hematological toxicities (18,23). Ceftazidime has been recommended as the drug of choice for the treatment of melioidosis on the basis of its good in vitro activity against P. pseudomallei (2, 7) and previous successes with the drug in a few noncomparative therapeutic trials (23,27). Our experience in an open multicenter trial also confirmed its efficacy and safety (20).…”
supporting
confidence: 56%
“…These drugs are also associated with serious renal and hematological toxicities (18,23). Ceftazidime has been recommended as the drug of choice for the treatment of melioidosis on the basis of its good in vitro activity against P. pseudomallei (2, 7) and previous successes with the drug in a few noncomparative therapeutic trials (23,27). Our experience in an open multicenter trial also confirmed its efficacy and safety (20).…”
supporting
confidence: 56%
“…Small numbers of cases of locally acquired melioidosis have been observed in Hong Kong (397,398,440,483), and a seroprevalence of 14% was demonstrated by IHA in a tuberculosis sanatorium (396). An ongoing outbreak in marine mammals in an ocean park has been described (193).…”
Section: Vietnam Melioidosis Was First Noted In What Is Now Southernmentioning
confidence: 99%
“…In the past decade, melioidosis in both human and other animals (dolphins and seals) has been reported from Hong Kong (140,141,165,175), and serological evidence indicates that human exposure to P. pseudomallei is not uncommon there (139). There is a dearth of information regarding the existence of melioidosis within mainland China.…”
Section: Introductionmentioning
confidence: 99%